Prevalence and timing of specialist palliative care access among advanced cancer patients and association with hospital death. (1st June 2022) - Yang, Grace Meijuan; Lim, Cindy; Zhuang, Qingyuan; Ong, Wah Ying
Background: Patients with advanced cancer have poor quality of life and high utilisation of acute healthcare services. Early access to palliative care has been shown to improve quality of life as well as reduce acute healthcare utilisation and costs. Objectives: To determine the prevalence and timing of hospital-based specialist palliative care reviews for patients with advanced cancer known to National Cancer Centre Singapore. We also explored the association between specialist palliative care review and place of death. Methods: A retrospective study of patients with Stage 4 cancer who died in a 2-year period from 1 January 2016 to 31 December 2017 (regardless of their date of diagnosis) and who received treatment in National Cancer Centre Singapore (NCCS). Results: A total of 2572 patients were included, of which 1226 (47.7%) had at least one inpatient or outpatient specialist palliative care consultation. Those who had their first specialist palliative care review 30 days or less before death had a 2.01 (95% CI 1.62 to 2.49, p < 0.001) increased odds of hospital death while those who had the first hospital-based palliative care review more than 30 days before death a 0.76 (95% CI 0.62 to 0.93, p = 0.009) reduced odds of hospital death. Conclusions: Our study found inadequate and late access to specialist palliative care among advanced cancer patients. Furthermore, late access to specialist palliative care was associated with hospital death. There is an urgent need to improve access to specialist palliative care in order to improve patient outcomes.